Electrochemical Deposited Nickel Nanowires: Influence of Deposition Bath Temperature on the Morphology and Physical Properties - Nurhanis Sofiah, Abd Ghafar; Kananathan, J.; Samykano, Mahendran; Ulakanathan, S.; S. A., Che Ghani; W. S., Wan Harun; Sudhakar, K.; K., Kadirgama; W. K., Ngui; Siregar, J. P. (IOP Publishing, 2017)
This paper investigates the influence of the electrolytic bath temperature on the morphology and physical properties of nickel (Ni) nanowires electrochemically deposited into the anodic alumina oxide porous membrane (AAO). The synthesis was performed using nickel sulfate hexahydrate (NiSO4.6H2O) and boric acid (H3BO3) as an electrolytic bath for the electrochemical deposition of Ni nanowires. During the experiment, the electrolyte bath temperature varied from 40°C, 80°C, and 120°C. After the electrochemical deposition process, AAO templates cleaned with distilled water preceding to dissolution in sodium hydroxide (NaOH) solution to obtain free-standing Ni nanowires. Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive Spectroscopy (EDX) and X-ray Diffraction (XRD) analysis were employed to characterize the morphology and physical properties of the synthesized Ni nanowires. Finding reveals the electrodeposition bath temperature significantly influences the morphology and physical properties of the synthesized Ni nanowires. Rougher surface texture, larger crystal size, and longer Ni nanowires obtained as the deposition bath temperature increased.